Additivity of the mechanical properties for acrylonitrile‐butadiene‐styrene resins. Issue 15 (17th November 2021) - Zhang, Huan; Ding, Fang; Liu, Tingli; Liu, Lunyang; Li, Yunqi
Abstract: Acrylonitrile‐butadiene‐styrene (ABS) resins have broad applications in automotive, transportation, and electronic industry attributed from their steadily tunable mechanical properties though varying compositions. It arises a question whether the additivity principle is applicable in their composition‐mechanical properties relationship. Here, we evaluated the applicability of the additivity principle for Young's modulus (YM), tensile strength (TS), and elongation at break (EB), based on a collection of 360 ABS resins from literatures and commercial products. We found that more than 90% of resins satisfy the additivity principle for YM and TS. While for EB, it varied from 14% to 100% depending on the combinations (A + B + S, AB + S, A + BS, or AS + B) and the contributed weights by mass, molar, or volume fractions. The majority of nonadditive resins have EB less than 20%, where the presence of the agglomeration of rubber phases, incompatible internal phases, cracks for those less ductile ABS resins are widely used qualitative and apparent reasons for the non‐predictable EB and the failure for the additivity principle. We then construct a classification model to distinguish the additive from nonadditive resins for EB, the area under the receiver operating characteristic curve (AUC) only achieves a fair value of 0.84. It further reveals that the fraction of acrylonitrile and butadiene, processing temperature, the length of spline, and the strain rate in the tensile test are important factors responsible for the failure of the additivity for EB. This study provides a quantitative reference to manipulate the mechanical properties for ABS resins beyond empirical evaluations. Abstract :